2019
DOI: 10.1002/ecs2.2943
|View full text |Cite
|
Sign up to set email alerts
|

Geographic isolation, pollination syndromes, and pollinator generalization in HimalayanRoscoeaspp. (Zingiberaceae)

Abstract: The pollination syndromes have been widely used to predict effective pollinators of plant species and provide the mechanistic explanation of floral diversity. However, in recent years, the predictive applicability of pollination syndromes has been frequently questioned. The accuracy of the syndromes among the closely related plant species may vary temporally and spatially. This suggests the need for the standardized, comprehensive evaluation of factors influencing the matching of a pollination syndrome of a pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 59 publications
(95 reference statements)
2
19
1
Order By: Relevance
“…The flowers were then left open to visitation by the potential floral visitors. Previous findings (Paudel et al., 2015, 2017, 2019) based on both observational data and bagging experiments suggest the absence of nocturnal pollinators to the study species. Thus, we focused our observation for diurnal visitors only.…”
Section: Methodsmentioning
confidence: 53%
See 3 more Smart Citations
“…The flowers were then left open to visitation by the potential floral visitors. Previous findings (Paudel et al., 2015, 2017, 2019) based on both observational data and bagging experiments suggest the absence of nocturnal pollinators to the study species. Thus, we focused our observation for diurnal visitors only.…”
Section: Methodsmentioning
confidence: 53%
“…Previous studies (Paudel et al., 2017, 2019) reveal that moths ( Macroglossum nycteris ) visit the flowers of R. alpina , R. capitata and R. tumjensis for nectar robbing, but do not facilitate their pollination. Bumblebees ( Bombus tanguticus ) and butterflies ( Pachliopta aristolochiae ) act as nectar robbers of R. auriculata .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fenster, Reynolds, Williams, Makowsky, & Dudash, 2015;Hargreaves, Johnson, & Nol, 2004;Rosas-Guerrero et al, 2014;Vandelook et al, 2019) and contradicting (e.g. Blüthgen, Menzel, Hovestadt, Fiala, & Blüthgen, 2007;Ollerton et al, 2009;Paudel, Kessler, Shrestha, Zhao, & Li, 2019;Rocha, Domingos-Melo, Zappi, & Machado, 2020;Wang, Wen, Qian, Pei, & Zhang, 2020) the validity of the pollination syndrome hypothesis. Researchers also demonstrated that pollination systems can show parallel adaptations to multiple pollinator groups (Dellinger, Scheer, et al, 2019), and thus suggested reclassification of some pollination syndromes (Dellinger, Chartier, et al, 2019), or proposed that pollination syndrome theory can be improved by other concepts, like optimal foraging theory or evolution stable strategy (Pyke, 2016).…”
Section: Introductionmentioning
confidence: 99%